2022
DOI: 10.3390/su142114451
|View full text |Cite
|
Sign up to set email alerts
|

Acid Resistance of Alkali-Activated Natural Pozzolan and Limestone Powder Mortar

Abstract: The development of sustainable, environmentally friendly alkali-activated binder has emerged as an alternative to ordinary Portland cement. The engineering and durability properties of alkali-activated binder using various precursor combinations have been investigated; however, no study has focused on the impact of high-volume natural pozzolan (NP) on the acid resistance of alkali-activated NP and limestone powder. Therefore, the current study assesses the impact of high-volume natural pozzolan (volcanic ash) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Several research conducted by Arif et al [45,47], Sothornchaiwit et al [49], and Jha et al [54] also found similar findings. In addition, research conducted by Al-Sodani et al [55] reported that the most significant resilience against acid attacks was witnessed when employing a substantial quantity of natural pozzolan. The calculation of percentage loss in compressive strength by Equation (4).…”
Section: Weight Loss Percentagementioning
confidence: 99%
“…Several research conducted by Arif et al [45,47], Sothornchaiwit et al [49], and Jha et al [54] also found similar findings. In addition, research conducted by Al-Sodani et al [55] reported that the most significant resilience against acid attacks was witnessed when employing a substantial quantity of natural pozzolan. The calculation of percentage loss in compressive strength by Equation (4).…”
Section: Weight Loss Percentagementioning
confidence: 99%